Risk Factors for Gall Stone Diseases in Patients Presenting to General Practice Out Patient Department in a Tertiary Care Center in Nepal - Neupane, Ram P.; Shrestha, Tirtha M; Raut, Shankar; Aacharya, Ramesh P (Journal of Institute of Medicine Nepal, 2019)
Introduction: Gallstone disease (GSD) is a major public health problem that is associated with a number of risk factors. This study aims to analyze the risk factors of GSD in patients visiting General Practice Outpatient Department of Tribhuvan Universtiy Teaching Hospital.Methods: A case-control study of 174 participants comprising 85 cases with GSD and 89 controls without GSD, as confirmed by ultrasonography of abdomen was conducted as hospital based in outpatient department of General practice, Tribhuvan University Teaching Hospital, Kathmandu from 1st February 2018 to 31st January, 2019. The participants were asked questions regarding putative risk factors for development of GSD and underwent physical and ultra sonographic examination. Risk factors included were age, sex, BMI, occupation, co-morbidities e.g. diabetes mellitus, hemolytic diseases, family history of GSD, smoking status, alcohol consumption, parity if applicable and dietary history. Data analysis was done by univariate method.Results: The mean age of the case group was 47.82 years whereas mean age for the control was 46.51 years (p=0.355). 22% of cases were male and 78% were female where as in control group 29% were male (p=0.3030). Majority of the participants in both group were housewife by occupation and Hindu by religion. Mean BMI of the cases and control were 24.05 kg/m2 and 21.13kg/m2 respectively. BMI was found significant for the gall stone diseases (p=